Sony gets hacked - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
This case describes how in April and May of 2011 the hacktivist group Lulzec repeatedly broke through Sony's cyber security to hack the company, costing them millions of dollars and representing a new kind of Internet crisis.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). Sony Gets Hacked. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 75-79). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Soni Kabushiki Kaisha; Crisis management -- Case studies; Hacking -- Case studies